Aluminum(I)/Boron(III) Redox Reactions. Issue 11 (11th February 2019) - Hofmann, Alexander; Pranckevicius, Conor; Tröster, Tobias; Braunschweig, Holger
Abstract: Reactions between B III species and the novel nucleophilic cyclopentadienyl‐stabilized Al I reagent (1 ) result in a diversity of complexes bearing different Al/B oxidation states and coordination geometries. With the triarylborane B(C6 F5 )3, a simple Al I →B III adduct is formed. In contrast, a bulky aryldihaloborane undergoes oxidative addition with the formation of a covalent bora‐alane species. With an N‐heterocyclic carbene‐stabilized amino(bromo)borenium ion, a redox reaction was observed, where the product is a borylene‐alane B I →Al III complex. Additionally, reaction of 1 with BI3 results in complete scrambling of all of the Al/B‐bound substituents, and the formation of a cyclopentadienylboron(I)→AlI3 complex. These latter reactions are the first examples of the reduction of a boron(III) compound to a borylene by a p‐block reagent, and illustrate how subtle changes in the nature of the borane can result in highly divergent reaction outcomes. Abstract : All good things come in threes : Reactions of an Al I nucleophile with B III species leads to three distinct modes of reactivity: adduct formation (Al I ‐B III ), oxidative addition (Al II ‐B II ), and reduction (Al III ‐B I ). IMes=1, 3‐dimesitylimidazol‐2‐ylidene, TerPh i Pr =bis‐2, 6‐(2, 4, 6‐triisopropylphenyl)phenyl.